CONCEPTUAL MODELLING OF GOLD AUTHENTICATION SYSTEM BASED ON ULTRASOUND PROPAGATION ANALYSIS - Zaidi, F.; Jamaludin, J.; Othman, M.; Ismail, I.; Tengku Abd Hafiz Pikry, T. M. K. (Journal of Engineering and Technology (JET), 2026)
his paper presents a simulation-based study of a non-destructive gold authentication system using ultrasonic wave propagation analysis. The system is developed and simulated in Visual Studio Code using Python-based tools. Simulation data is obtained from COMSOL Multiphysics, utilizing a 5 MHz ultrasonic sensor. The total acoustic pressure (Pa) is extracted as a key feature for statistical analysis, employing metrics such as Mean Squared Error (MSE), Root Mean Squared Error (RMSE), and Correlation Coefficient. Gold purity classification is performed through comparative analysis between data from pure gold and gold alloyed with tungsten or silver. The results demonstrate high accuracy in purity identification and highlight the potential of the proposed system for practical real-time applications.